2008
DOI: 10.11646/zootaxa.1686.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The “Celestial Pearl danio” is a miniature Danio (s.s) (Ostariophysi: Cyprinidae): evidence from morphology and molecules

Abstract: The osteology of the miniature cyprinid Celestichthys margaritatus Roberts, type species of Celestichthys Roberts, is described in detail and briefly compared with that of other members of the Rasborinae (notably Danio (s.s), Danionella, Devario, Esomus, Microrasbora, Paedocypris and Sundadanio). Celestichthys margaritatus possesses an “A” stripe on the anal fin and two pigment stripes on the caudal fin (apomorphic features of Danio sensu Fang, 2003). In addition, C. margaritatus exhibits a median projection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
58
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(77 citation statements)
references
References 29 publications
19
58
0
Order By: Relevance
“…Various recent molecular phylogenetic studies with increased taxon and character (gene loci) sampling Mayden et al, 2007Mayden et al, , 2008Mayden et al, , 2009Conway et al, 2008), however, have consistently revealed resolved clades in the suborder Cyprinoidea that have now been formally recognized by Chen and Mayden (2009) as families or clades. While there are discrepancies between phylogenetic relationships resolved using cytb (Cunha et al, 2002;Rüber et al, 2007) and S7 (this study and He et al, 2008) regarding cyprinoid evolution, the historical ''subfamily" designations within the suborder Cyprinoidea (formerly family Cyprinidae sensu Chen and Mayden, 2009) were not based on rigorous phylogenetic evaluations but were groupings of largely morphologically similar and dissimilar taxa that are now being resolved as both clades and grades (sensu Saitoh et al, 2006;Mayden et al, 2007Mayden et al, , 2008Mayden et al, , 2009Conway et al, 2008;Chen and Mayden, 2009). Studies with more comprehensive data sets are emerging, both in terms of taxa and characters, and these will be necessary to continue to develop a deeper understanding of the interesting evolutionary history of the world's most diverse clade of freshwater fishes, order Cypriniformes.…”
Section: Discussionmentioning
confidence: 99%
“…Various recent molecular phylogenetic studies with increased taxon and character (gene loci) sampling Mayden et al, 2007Mayden et al, , 2008Mayden et al, , 2009Conway et al, 2008), however, have consistently revealed resolved clades in the suborder Cyprinoidea that have now been formally recognized by Chen and Mayden (2009) as families or clades. While there are discrepancies between phylogenetic relationships resolved using cytb (Cunha et al, 2002;Rüber et al, 2007) and S7 (this study and He et al, 2008) regarding cyprinoid evolution, the historical ''subfamily" designations within the suborder Cyprinoidea (formerly family Cyprinidae sensu Chen and Mayden, 2009) were not based on rigorous phylogenetic evaluations but were groupings of largely morphologically similar and dissimilar taxa that are now being resolved as both clades and grades (sensu Saitoh et al, 2006;Mayden et al, 2007Mayden et al, , 2008Mayden et al, , 2009Conway et al, 2008;Chen and Mayden, 2009). Studies with more comprehensive data sets are emerging, both in terms of taxa and characters, and these will be necessary to continue to develop a deeper understanding of the interesting evolutionary history of the world's most diverse clade of freshwater fishes, order Cypriniformes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the name Rasborinae has seen widespread use instead of Danioninae (e.g. Gosline, 1975Gosline, , 1978Howes, 1979Howes, , 1980aHowes, , 1983Howes, , 1991Fink and Fink, 1981;Cavender and Coburn, 1992;Nelson, 1994Nelson, , 2006Mayden et al, 2007Mayden et al, , 2008Rüber et al, 2007;Conway et al, 2008). The family-group name Danioninae dates back to Bleeker (1863a), who assigned the name Daniones, an infrafamilial name of uncertain rank, for the genera Danio and Luciosoma.…”
Section: Introductionmentioning
confidence: 99%
“…Danionella, Paedocypris), as well as a large-scale Assembling the Tree of Life project directed at the order Cypriniformes, have all led to a increase in the number of phylogenetic analyses involving this subfamily in the past few years (e.g. Mayden et al, 2007;Rüber et al, 2007;Conway et al, 2008Conway et al, , 2009Fang et al, 2009;Mayden and Chen, in press). This activity has greatly improved our understanding of the relationships within this group, but there is lingering uncertainty about the exact composition and relationships of the Danioninae, as many of these studies produced conflicting and/or equivocal results for the phylogeny of the group.…”
Section: Introductionmentioning
confidence: 99%
“…Along the anterior two thirds of its dorsal margin is also a narrow groove with foramina sitting in the bottom. The groove seems in continuation with that in the anterior ceratohyal, possibly for the hyoidean artery to traverse [45]. Its ventral margin is blade-like.…”
Section: Methodsmentioning
confidence: 86%
“…The way of measurements of the pharyngeal bone follows Chu [43] and the terms of teeth are according to Vasnetsov [44]. General osteological terminology follows that of Conway et al [45]. Dentary: Seventeen left and 15 right dentaries were recognized, but none of them is intact.…”
Section: Methodsmentioning
confidence: 99%